Parasite antigens: Summary and proceedings of an international workshop - Westley, S.B.; Howe, V. (International Laboratory for Research on Animal Diseases, 1985)
Parasitic diseases cause serious illness and often death in human populations and domestic livestock, particularly in the tropics. These include malaria, trypanosomiasis and tick-borne diseases. Important recent developments in the fields of immunology, biochemistry and molecular biology might make it possible to control some of these diseases. This workshop on parasite antigen was held to review the current status of research aimed at characterizing, producing and utilizing parasite antigens which could lead to the improved control of parasitic diseases; to identify constraints which impede the progress of this research; and to explore new approaches towards the solution of these major disease problems. Major topics of discussion are approaches to identification and characterization of potentially protective antigens; identification and expression of antigens genes; induction of protective response; and new approaches to diagnosis of parasitic diseases.